CONSTRUCTION OF COVID-19 PANDEMIC MANAGEMENT POLICY BASED ON THE WELFARE OF WOMEN AND CHILDREN - Prasetyo, Dimas Aji; Juanito, Juanito; Hapsari, Adinda Mustika; Natalis, Aga (Universitas Semarang, 2021)
The purpose of this study is to find out and analyze the construction of policies for handling the Covid-19 pandemic based on women and children's welfare and analyze the Government's role in realizing the policy for handling the Covid-19 pandemic. In order to realize the welfare of women and children. This study uses a qualitative method with a normative juridical approach. The results showed that the construction of welfare-based Covid-19 handling policies for women and children must be socialized to women and children. The socialization process to women and children is carried out in a way; love, appreciation, and love between family members. Socializing women and children in making a policy must encourage and enable women and children to collaborate as equal stakeholders in policies to handle Covid-19 during the pandemic. This policy has certain limitations, such as Human Rights, Good Governance, and Morality. Policies with these limitations will produce policies that guarantee freedom for women and children, protection for women and children, welfare for women and children, child development, all of which must be considered in the policy for handling Covid 19.